the CASE REPORT: SEVERE HYPOCHROMIC MICROCYTIC ANEMIA CAUSED BY IRON DEFICIENCY ANEMIA - nyoman, sabna; Ida Bagus Wemanu Ngaling; Ni Nyoman Mestri Agustini; I Made Kesuma Wijaya (Universitas Aufa Royhan, 2025)
Iron deficiency anemia (IDA) is the most common type of anemia caused by insufficient iron for hemoglobin synthesis, leading to impaired oxygen transport in the body. This study aims to report and analyze a case of severe iron deficiency anemia in a 63-year-old female patient with comorbid hypertensive heart disease. The research method was a case study involving data collection from anamnesis, physical examination, laboratory tests (Hb, MCV, MCH, ferritin, and serum iron), and supporting radiologic examinations such as chest X-ray and electrocardiography. The results showed Hb 5.4 g/dL, MCV 69.3 fL, MCH 19.7 pg, ferritin 4.3 µg/L, and serum iron 10.8 µg/dL, indicating severe hypochromic microcytic anemia due to iron deficiency. The patient received oxygen therapy, packed red cell transfusions until Hb reached 10 g/dL, oral ferrous sulfate 200 mg three times daily, and vitamin C 100 mg three times daily, along with supportive care, resulting in significant clinical and laboratory improvement after eight days of hospitalization. This case highlights the importance of early diagnosis and prompt management to prevent systemic complications of iron deficiency anemia.